2023
DOI: 10.1002/2688-8319.12255
|View full text |Cite
|
Sign up to set email alerts
|

Arduinos in the wild: A novel, low‐cost sensor network for high‐resolution microclimate monitoring in remote ecosystems

Lina K. Mühlbauer,
Giorgio Zavattoni,
Risto Virtanen
et al.

Abstract: The importance of microclimate conditions is becoming increasingly recognised in ecological research, especially as they can differ widely from macro‐ and mesoclimate. Effective measurement of microclimate variability in heterogeneous field conditions requires measurements from a large number of sensors, ideally sampling across both small and large scales, which necessitates the development of cost‐effective sensor networks. Here, we develop an environmental microcontroller (EMU) sensor network for measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The performance was higher than that recorded by (Novais et al, 2020), who reached R 2 = 0.91 in the calibration of air humidity sensors. Thus, the relative humidity measurement method developed represents an accurate and accessible alternative for environmental monitoring in animal production and allows the detection of microclimatic fluctuations with low sampling error, generating reliable data for management in facilities, as required by (Mühlbauer et al, 2023). (Mander et al, 2023) The variation in observed values, from 300 to 1000 lux, is substantially above the recommendations established by (Barros et al, 2020) for laying hens (5 to 50 lux), whereas for broiler chickens in the final phase, it should not exceed 5 lux (Wu et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The performance was higher than that recorded by (Novais et al, 2020), who reached R 2 = 0.91 in the calibration of air humidity sensors. Thus, the relative humidity measurement method developed represents an accurate and accessible alternative for environmental monitoring in animal production and allows the detection of microclimatic fluctuations with low sampling error, generating reliable data for management in facilities, as required by (Mühlbauer et al, 2023). (Mander et al, 2023) The variation in observed values, from 300 to 1000 lux, is substantially above the recommendations established by (Barros et al, 2020) for laying hens (5 to 50 lux), whereas for broiler chickens in the final phase, it should not exceed 5 lux (Wu et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The libraries to control these modules are usually in C++, making them difficult to understand and use. Some Arduino models, such as the MKR1310, seek to simplify LoRa prototyping [17]. However, their limited availability and high cost can be disadvantages.…”
Section: Introductionmentioning
confidence: 99%